2021
DOI: 10.17306/j.afs.0771
|View full text |Cite
|
Sign up to set email alerts
|

Development of chitosan edible film incorporated with Chrysanthemum morifolium essential oil

Abstract: Background. Biodegradable food packaging has improved in quality with recent research incorporating natural extracts for functionality purposes. This research aims to develop chitosan film with Chrysanthemum morifolium essential oil to improve the shelf life of fresh raw chicken and beef. Materials and methods. 1.5% (w/v) chitosan films with Chrysanthemum morifolium essential oil (0% to 6% (v/v)) were produced through homogenization, the casting of a film solution in a petri dish and convection drying. The edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
(48 reference statements)
2
17
0
Order By: Relevance
“…The increase of the film thickness when GsO increases could be associated with the increase of the total solids in the chitosan / GsO emulsion system. Similar results were reported by Tan [25] who postulated that the essential oil filled a chitosan matrix caused the value of thickness to increase. The moisture barrier properties of the edible films are one of the most important for their application as food packaging material.…”
Section: Films Physico-chemical Characteristicssupporting
confidence: 88%
“…The increase of the film thickness when GsO increases could be associated with the increase of the total solids in the chitosan / GsO emulsion system. Similar results were reported by Tan [25] who postulated that the essential oil filled a chitosan matrix caused the value of thickness to increase. The moisture barrier properties of the edible films are one of the most important for their application as food packaging material.…”
Section: Films Physico-chemical Characteristicssupporting
confidence: 88%
“…More so, the added rice husk ash has the possibility of not entirely dispersing in the solder after soldering. In the molten state, these foreign particles may be rejected, engulfed or entrapped, depending on the reinforcing agent and solder interaction mechanisms [31]. This reasoning can be proved with the fracture surface images showing the presence of silica on the fracture surface that will be discussed in the subsequent section.…”
Section: Resultsmentioning
confidence: 76%
“…Antioxidant and antibacterial agents from PE extracted using different solvents such as ethanol, methanol, and aqueous were previously incorporated into EF [6,22,23]. EOs from AP are also commonly extracted using hydro-distillation for use in natural medicine or natural food preservation [14,21]. Recent studies have shown that incorporating these extracts into different biopolymers (polysaccharides, protein, and lipids) could help in enhancing the qualities of active EF.…”
Section: Ef Formulations Containing Different Ape and Eosmentioning
confidence: 99%
“…Table 1 lists examples of the various APE and EOs incorporation of EF. Various APE (e.g., black soybean, Chrysanthemum morifolium, Eriobotrya japonica Lindl., ginger, turmeric and plai, hawthorn berry, kiam, mangosteen, neem, Moringa oleifera Lam., Piper Betle Linn., and Sophora japonica) have been selected to incorporate into different polymer-based EFs to improve the functional properties of food packaging [5][6][7][9][10][11][12]14,15,22,[24][25][26]. According to the review, many studies have extracted APE with ethanol for incorporation into various biopolymer-based EFs (alginate, chitosan, and gelatin).…”
Section: Ef Formulations Containing Different Ape and Eosmentioning
confidence: 99%
See 1 more Smart Citation